BURNOUT AND RELATED FACTORS IN HOSPITAL HEALTH WORKERS AFTER ONE YEAR OF COVID-19 PANDEMIC - Wening Tri Mawanti; Astrid Sulistomo; Fijar Mohamad; Marsha Vania; Nofrizal N. (Binawan Student Journal, 2023)
Workload, fear of contracting Covid-19 or the use of high levels of personal protective equipment which causes discomfort and exhaustion are some of the potential factors that can cause burnout in hospital health workers. The aims of this study were to determine the prevalence and factors related to burnout in hospital health workers after one year of the covid-19 pandemic. This study used a cross-sectional design and the Indonesian version of the Maslach Burnout Inventory (MBI) questionnaire to diagnose burnout. In the Masclach Burnout Inventory (MBI) questionnaire, burnout is grouped into the following three dimensions: a) emotional fatigue, b) loss of empathy, and c) self-esteem. The MBI questionnaire was distributed using a Google form (G-form). Data processing and analysing was conducted using SPSS version 20.0 program. A total of 135 health workers filled out the G-form questionnaire and it was found that 39.3% of them experienced burnout.  Factors significantly related (p<0,05) to burnout were higher education with ORa 4.10 (95% C.I.= 1.66 – 7.27) and shift work with ORa 2.44 (95% C.I.= 1.02 -5.86). The prevalence of burnout for health workers at the one of private Hospital in East Jakarta after more than 1 year of the Covid-19 pandemic was 39.3%. Factors that are significantly related to burnout are the level of education and shift work patterns.